2021
DOI: 10.1159/000519822
|View full text |Cite
|
Sign up to set email alerts
|

Association between Preoperative Monocyte-to-Lymphocyte Ratio and Late Arteriovenous Fistula Dysfunction in Hemodialysis Patients: A Cohort Study

Abstract: <b><i>Background:</i></b> Inflammation appears to be at the biological core of arteriovenous fistula (AVF) dysfunction, and the occurrence of AVF dysfunction is related to high death and disability in hemodialysis (HD) patients. Despite several studies on the correlations between AVF dysfunction and inflammatory indicators, how AVF dysfunction is related to the monocyte-to-lymphocyte ratio (MLR) is much unclear. We hypothesize that preoperative MLR is associated with AVF dysfunction in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
(39 reference statements)
1
5
0
Order By: Relevance
“…Thus, combining monocytes and lymphocytes seems to be a good strategy to evaluate inflammation and it may react with high sensitivity on even minor changes in uremic settings. Therefore, in dialysis patients, MLR was not only related to the hospitalization risk of GI disorder in this study but also related to cardiovascular events, infectious diseases, late arteriovenous fistula dysfunction, mortality of CVD, and all-cause mortality in other studies [11,15,[41][42][43].…”
Section: Discussionsupporting
confidence: 51%
“…Thus, combining monocytes and lymphocytes seems to be a good strategy to evaluate inflammation and it may react with high sensitivity on even minor changes in uremic settings. Therefore, in dialysis patients, MLR was not only related to the hospitalization risk of GI disorder in this study but also related to cardiovascular events, infectious diseases, late arteriovenous fistula dysfunction, mortality of CVD, and all-cause mortality in other studies [11,15,[41][42][43].…”
Section: Discussionsupporting
confidence: 51%
“…Studies have demonstrated that higher monocyte/lymphocyte ratios are associated with AVF dysfunction. Similarly, Hu et al 20 found a significant association between elevated monocyte/lymphocyte ratios and AVF stenosis, a condition leading to AVF dysfunction.…”
Section: Discussionmentioning
confidence: 84%
“…AVF dysfunction in hemodialysis can result from thrombosis or clotting within the fistula, disrupting blood flow and impeding treatment. Elevated prothrombin activity and lower prothrombin time in the AVF 20 found a significant association between elevated monocyte/lymphocyte ratios and AVF stenosis, a condition leading to AVF dysfunction.…”
Section: Discussionmentioning
confidence: 87%
“…The monocyte-to-lymphocyte ratio (MLR) is defined as the absolute number of monocytes divided by the absolute number of lymphocytes. Several studies have found a positive correlation between MLR and AVF immaturity ( 43 ). The release of macrophage migration inhibitor factor (MIF) up-regulates tumor necrosis factor (TNF) -α, interleukin (IL) -6, IL-8 and MCP-1 and other inflammatory cytokines, causing the migration and proliferation of inflammatory cells and promoting NIH ( 19 ).…”
Section: Different Types Of Immune Cells Are Involved In Vascular Rem...mentioning
confidence: 99%